Peningkatan kemampuan motorik halus melalui permainan menganyam dari bahan alam di taman kanak – kanak cahaya hati kabupaten pasaman barat - Meli Susanti (JRTI (Jurnal Riset Tindakan Indonesia), 2019)
This study used Classroom Action Research conducted in Light Heart Kindergarten. This research was conducted for 2 months, namely as many as 2 cycles, namely cycle I consisted of 3 meetings and cycle II consisted of 3 meetings. Data collection with observations, interviews, and documentation were analyzed by percentage techniques. The results of observations on the initial conditions indicate that the children's fine motor skills are still low. The implementation of the first cycle of the first meeting until the third meeting showed an increase in the fine motor skills of the child, but had not been able to reach the KKM so that the second cycle was carried out. After the second cycle, the first meeting until the third meeting, there was a significant increase in the children's fine motor skills, especially in the aspect of children. They could move their fingers when weaving. Childhood Light Heart of West Pasaman.